Linking positive childhood experiences to young adults' communication and problem-solving skills: The mediating role of self-confidence - Bilgin, Okan; Ince, Murat (ELSEVIER, 2026)
Positive experiences in early life stages are increasingly recognized as foundational elements that shape individuals' psychological resources and social competencies throughout adulthood. This study examined the impact of positive childhood experiences on young adults' communication and problem-solving skills, focusing on the mediating role of self-confidence. Participants included 696 university students (580 females, 116 males; M age = 22.1), who completed validated measures of positive childhood experiences, self-confidence, communication, and problem-solving. Structural equation modeling revealed that the influence of positive childhood experiences on communication and problem-solving skills was entirely indirect, fully mediated by selfconfidence, with no significant direct effects. Additionally, self-confidence significantly predicted both skills. A gender difference favoring females was found only in communication skills. These findings underscore the importance of fostering self-confidence as a developmental outcome of positive early experiences and contribute to understanding how childhood shapes essential competencies in emerging adulthood.
Keywords: Positive childhood experiences; Self-confidence; Communication skills; Problem solving skills; Psychology